Direct Conversion of Fe2O3 to 3D Nanofibrillar PEDOT Microsupercapacitors. (9th June 2020) - Diao, Yifan; Lu, Yang; Yang, Haoru; Wang, Hongmin; Chen, Haozhe; D'Arcy, Julio M.
Abstract: Microsupercapacitors (µSCs) are attractive electrochemical energy storage devices serving as alternatives to batteries in miniaturized portable electronics owing to high‐power density and extended cycling stability. Current state‐of‐the‐art microfabrication strategies are limited by costly steps producing materials with structural defects that lead to low energy density. This paper introduces an electrode engineering platform that combines conventional microfabrication and polymerization from the vapor phase producing 3D µSCs of the conducting polymer poly(3, 4‐ethylenedioxythiophene) (PEDOT). A sputtered Fe2 O3 precursor layer enables deposition of a 250 nm thick polymer coating comprised of a high packing density of vertically aligned PEDOT nanofibers possessing exceptional electrical conductivity (3580 S cm −1 ). The 3D µSCs exhibit state‐of‐the‐art volumetric energy density (16.1 mWh cm −3 ) as well as areal (21.3 mF cm −2 ) and volumetric (400 F cm −3 ) capacitances in 1 m H2 SO4 aqueous electrolyte. These figures of merit represent the highest values among conducting polymer‐based µSCs. Electrochemical performance is controlled by investigating coating thickness, gap distance, fractal geometry, and gel electrolyte (1 m H2 SO4 /polyvinyl alcohol). The quasisolid‐state µSCs exhibit extended rate capability (50 V s −1 ), retain 94% of original capacitance after 10 000 cycles and remain thermally stable up to 60 °C. Abstract : This paper presents a superior and cost‐effective strategy for developing 3D microsupercapacitors that directly convert Fe2 O3 to poly(3, 4‐ethylenedioxythiophene) (PEDOT) nanofibers in one step. The PEDOT nanofibers possess a vertical aligned structure enabling exceptional conductivity of 3580 S cm −1 . The device exhibits the highest energy density reported among organic material‐based microsupercapacitors and retain 94% of the original capacitance after 10 000 cycles.